2004
DOI: 10.1007/s00198-003-1499-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social deprivation, osteoporosis, and falls

Abstract: The aim of this study was to assess the relationship between heel BMD, risk factors for osteoporosis, falls history, and the Jarman Underprivileged Area Score in an older community population. From the general practice register, 1,187 women (mean age 70, range 60 to 94) were recruited. BMD of the heel was measured using the GE Lunar PIXI densitometer. A T-score cutoff for predicted osteoporosis at the spine or hip of -1.7 was used. A risk factor questionnaire was completed that included fracture history and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, a previous study has shown lower rates of hip fracture with increased deprivation, with these differences put down to differences in age between groups [ 51 ]. Though a previous study had suggested that people from more deprived groups were more likely to have a lower bone mineral density, with the only clearly difference in risk factors that hey smoked more [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study has shown lower rates of hip fracture with increased deprivation, with these differences put down to differences in age between groups [ 51 ]. Though a previous study had suggested that people from more deprived groups were more likely to have a lower bone mineral density, with the only clearly difference in risk factors that hey smoked more [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1418] Lower SES is also associated with lower bone density in adult women [19] and increased adult fracture risk in osteoporosis. [20] On a neighborhood level, Canadian studies have shown that children who live in low-income neighborhoods exercise less and have less healthy diets than those living in more affluent neighborhoods, even after adjusting for family SES. [13] Studies of the effect of such community poverty on childhood fracture risk are limited and have yielded inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Although, women are more likely to suffer from osteoporosis, 10 those in the least deprived quartile of the population had significantly higher heel Bone Mineral Density (BMD) compared with the rest of the population. 41 Women in this quartile were also significantly less likely to smoke, indicating a relationship between gender, smoking, deprivation and osteoporosis. Socioeconomic deprivation was also found to be a risk factor for osteoporosis in older adults.…”
Section: Discussionmentioning
confidence: 90%